Upaya Peningkatan Pengetahuan Kader Tentang Cara Pemantauan Perkembangan Anak Balita Selama Masa Pandemi Covid-19 menggunakan Kuesioner Pra Skrining Perkembangan (KPSP) - Emy Sutiyarsih; Narita Diatanti (Borneo Community Health Service Journal, 2022)
During the Covid-19 pandemic, Posyandu for toddlers cannot be carried out optimally, while toddlers are an important period in the growth and development of children and are included in the critical stage of child development. Monitoring the development of children under five is very important to be done regularly in order to detect early developmental disorders so that appropriate and fast management can be carried out. One of the ways to monitor the development of toddlers is using the Developmental Pre-Screening Questionnaire (KPSP) in the form of a simple questionnaire that can be carried out by health cadres as an extension of the health workers. Servants intend to hold kader training which will be held for 3 times, namely 21, 22, 23 December 2021. The purpose of this activity is to broaden the knowledge of health kader on how to monitor the development of toddlers using KPSP. Before and after the training activities, tests were conducted as a tool for evaluation. The results of the pretest showed that most of the kader' knowledge was lacking 81.25%, some 18.75% was sufficient. The results of the post-test knowledge of lack of knowledge of cadres are sufficient to very good. This proves that there has been an increase in the knowledge of health cadres in understanding how to monitor the development of children under five using KPSP. All health cadres participate in the training enthusiastically and always follow the direction of the service, with the hope that the kader can carry out their duties with the assistance of health workers in Tambakasri Village. Keyword: toddlers,kader,  Monitoring the development